Permafrost. The Contemporary Meaning of the Term and its Consequences - Dobiński, Wojciech (Bulletin of Geography. Physical Geography Series, 2012)
Nowadays the term ‘permafrost’ means the thermal state of the ground, for which the temperature limit value is 0°C remaining for at least two years. It is the effect of the climate where the average annual temperature of the air is -1°C or lower. As a result of air temperature, it does not need to contain ice, so it can no longer be called underground glaciation, and the only processes which are subject to permafrost are aggradation and degradation. Also the occurrence of permafrost in the geographical environment is conditioned neither by the presence of water nor its phase change - freezing, as the cryotic state is its synonym. Although it is known that the majority of permafrost dates back to the Pleistocene, still the determination of its age is difficult because it consists in determining ‘the age of the temperature’, as it were. The maximum thickness of permafrost occurs in the Antarctic, and it is estimated to reach 2600 m. Permafrost covers more than 25% of the Earth surface together with ice-sheets and ice-caps.